Facile Synthesis of a New Class of Pyrazolone Attached Chromene Derivatives Showing Good Binding with β‐Lactoglobulin. Issue 18 (14th May 2018) - Guha, Chayan; Sepay, Nayim; Mallik, Sumitava; Mallik, Asok K.
Abstract: A new class of compounds having both chromene and pyrazolone moieties in the structural motif has been developed starting from 2‐hydroxychalcones and pyrazolones using amberlyst‐15 as a heterogeneous catalyst. The methodology involves a domino sequence of Michael addition, cyclisation, dehydration and aerial oxidation. Most of the compounds thus synthesised show good binding with the carrier protein β‐lactoglobulin. Molecular docking study of the compound showing best binding with the protein has been carried out. Abstract : An efficient synthesis of a new class of pyrazolone attached chromenes has been developed starting from 2‐hydroxychalcones and pyrazolones under the catalysis of amberlyst‐15 in aerial condition. The methodology involves a domino sequence of Michael addition, cyclisation, dehydration and aerial oxidation. Most of these compounds show good binding with β‐lactoglobulin.